STRATEGIES FOR THE VALIDATION OF STEAM STERILIZATION PROCESS IN AUTOCLAVES FROM THE PHARMACEUTICAL INDUSTRY: Pharmaceutical Science-Analytical Chemistry - LEONARDO TEIXEIRA RODRIGUES; ADERVAL SEVERINO LUNA; CRISTIANE ASSUMPÇÃO HENRIQUES; AUGUSTO DA COSTA, ANTONIO CARLOS (International Journal of Life Science and Pharma Research, 2012)
The process of sterilization in the asepsis pharmaceutical ensures the materials used in the production of medicines. The method of saturated steam sterilization is always the first choice in the pharmaceutical industry because it is the most effective, faster, with better cost / benefit and with less environmental impact. In order to ensure necessary sterility, the qualification of autoclaves and validation of requirements when their loads are required by national and international regulatory bodies. The regulations of these bodies are not always objective and clear, indicating what should be done without specifying how it should be done. The focus of this work was to create a validation methodology, change control and revalidation in horizontal autoclaves, highlighting the critical points of the process, exploring the theoretical concepts of bioengineering. For this, we used statistical techniques for analyzing data collected in a study of thermal distribution, heat penetration and microbiological challenges to determine a fast, safe and effective that meets the requirements of regulatory bodies without affecting the production capacity of industrial plants and quality of the sterilization process.